Selective determination of poly(styrene) and polyolefin microplastics in sandy beach sediments by gel permeation chromatography coupled with fluorescence detection. (November 2018) - Biver, Tarita; Bianchi, Sabrina; Carosi, Maria Rita; Ceccarini, Alessio; Corti, Andrea; Manco, Enrico; Castelvetro, Valter
Abstract: Microplastics generated by plastics waste degradation are ubiquitous in marine and freshwater basins, posing serious environmental concerns. Raman and FTIR spectroscopies, along with techniques such as pyrolysis-GC/MS, are typically used for their identification. We present a procedure based on gel permeation chromatography (GPC) coupled with fluorescence detection for semi-quantitative selective determination of the most common microplastics found in marine shoreline sediments: poly(styrene) (PS) and partially degraded polyolefins (LDPEox). By operating the detector at either 260/280 or 370/420 nm excitation/emission wavelengths PS can be distinguished from LDPEox upon GPC separation. Semi-quantitative determination of microplastics contents is also possible: dichloromethane extracts of PS and LDPEox yield linear plots of fluorescence peak area vs concentration (0–5.0 mg/mL range) and were used as reference materials for quantification of the microplastics content in sand samples collected in the winter berm and dune sectors of a Tuscany beach in Italy. Graphical abstract: Highlights: Microplastics accumulation ashore is largely based on low density hydrocarbon polymers Quantitative determination of microplastics from marine sediments requires suitable analytical protocols Chromatographic separation with spectrofluorometric detection allows selective semi-quantitative analysis of poly(styrene) and degraded polyolefins Unprecedented semi-quantitative and selective determination of microplastics from shoreline sand sediments is achieved